Accelerated biocorrosion of stainless steel in marine water via extracellular electron transfer encoding gene phzH of Pseudomonas aeruginosa. (15th July 2022) - Zhou, Enze; Zhang, Mingxing; Huang, Ye; Li, Huabing; Wang, Jianjun; Jiang, Guangming; Jiang, Chengying; Xu, Dake; Wang, Qiang; Wang, Fuhui
Highlights: phzH gene regulates the corrosion rate of marine Pseudomonas aeruginosa . phzH gene regulates the secretion of phenazine-1-carboxamide (PCN). PCN affects the sessile cell count, which does not affect the corrosion tendency. PCN damages the passive film by facilitating the release of hexavalent chromium. EET mediated by PCN is the dominant factor to accelerate MIC. Abstract: Microbiologically influenced corrosion (MIC) constantly occurs in water/wastewater systems, especially in marine water. MIC contributes to billions of dollars in damage to marine industry each year, yet the physiological mechanisms behind this process remain poorly understood. Pseudomonas aeruginosa is a representative marine electro-active bacterium, which has been confirmed to cause severe MIC on carbon steel through extracellular electron transfer (EET). However, little is known about how P. aeruginosa causes corrosion on stainless steel. In this study, the corrosivity of wild-type strain, phzH knockout, phzH complemented, and phzH overexpression P. aeruginosa mutants were evaluated to explore the underlying MIC mechanism. We found the accelerated MIC on 2205 duplex stainless steel (DSS) was due to the secretion of phenazine-1-carboxamide (PCN), which was regulated by the phzH gene. Surface analysis, Mott-Schottky test and H2 O2 measurement results showed that PCN damaged the passive film by forming H2 O2 to oxidize chromium oxide to soluble hexavalent chromium, leading to more severe pitting corrosion. The normalized corrosion rate per cell followed the same order as the general corrosion rate obtained under each experimental condition, eliminating the influence of the total amount of sessile cells on corrosion. These findings provide new insight and are meaningful for the investigation of MIC mechanisms on stainless steel. The understanding of MIC can improve the sustainability and resilience of infrastructure, leading to huge environmental and economic benefits. Graphical abstract: Image, graphical abstract